2001
DOI: 10.1046/j.1537-2995.2001.41030390.x
|View full text |Cite
|
Sign up to set email alerts
|

Serial granulocytapheresisunder daily administration of rHuG–CSF: effects on peripheral blood counts, collection efficiency, and yield

Abstract: Repetitive daily rHuG-CSF administration-even under daily leukapheresis procedures-results in a continuing increase in WBC and neutrophil levels and thus leads to increased collection yields. Side effects are tolerable, although Hb and platelet levels should be monitored closely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…None of our donors with bone pain required medication. Our data are in line with Worel et al, who reported on mild adverse effects in granulocyte donors under daily administration of G-CSF: bone pain, headache, arthalgia, and myalgia were the most commonly observed side effects (n ¼ 18, 24%), but they were transient [13]. Bux and co-workers also reported on mild side effects in G-CSF stimulated donors but the rate of G-CSF related side effects increased from 58% after the first administration to 63% after the fourth administration [9].…”
Section: Discussionsupporting
confidence: 93%
“…None of our donors with bone pain required medication. Our data are in line with Worel et al, who reported on mild adverse effects in granulocyte donors under daily administration of G-CSF: bone pain, headache, arthalgia, and myalgia were the most commonly observed side effects (n ¼ 18, 24%), but they were transient [13]. Bux and co-workers also reported on mild side effects in G-CSF stimulated donors but the rate of G-CSF related side effects increased from 58% after the first administration to 63% after the fourth administration [9].…”
Section: Discussionsupporting
confidence: 93%
“…Comparable with our findings, several investigators who administered G-CSF at doses of 5, 7.5, or 10 lg/kg reported mild to moderate adverse effects such as bone pain, headache, arthralgia, and myalgia [8][9][10][11][12][13][14][15]29]. The more recent addition of DXM to the G-CSF regimen has resulted in similar symptom complexes with additional side effects, such as insomnia and nausea [5][6][7][8]17,19,28].…”
supporting
confidence: 89%
“…Most of our recipients are pediatric patients with a low body weight. Thus, volume reduction is necessary to avoid a transfusion overload in these patients . At our institution a product volume exceeding 500 mL must be divided into two parts before further processing.…”
Section: Discussionmentioning
confidence: 99%
“…The value of granulocyte transfusions (GTs) in patients with neutropenia with bacterial or fungal infections is still controversial. Although to date the beneficial effect of GT has not been proven in prospective randomized trials, in specific situations GT is an option to treat infections along with antibiotics when there is profound neutropenia . However, prophylactic transfusions are still a matter of discussion .…”
mentioning
confidence: 99%